Development of Science E-books Based on Local Wisdom to Improve Digital Literacy and Students' Critical Thinking Skills as An Innovation to Improve Education Sustainable Developments Goals (ESDG) - Satutik Rahayu; Muntari Muntari; Ahmad Harjono; Muh Makhrus; Muh. Zikron Kurniadin; Sarwanto Sarwanto; Siti Hasmah Mohtar (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to produce a science e-book based on local wisdom that is feasible, practical, and effective to improve students' digital literacy and critical thinking skills. This research method is a development research using the 4D model. The subjects of this study were grade VIII students at one of the Mataram City Public Junior High Schools consisting of 3 classes. Data collection techniques used questionnaires, observation sheets and test instruments developed according to critical thinking and digital literacy indicators. Data analysis techniques used Aikens'V for the feasibility test, practicality percentage test and normalized gain test to test the hypothesis. Based on the results of the study, it was found that the science e-book based on local wisdom that was developed was included in the category of feasible, practical and effective for use in science learning and could improve students' digital literacy and critical thinking skills. Science e-books based on local wisdom support students in the learning process by utilizing technology. The use of science e-books based on local wisdom makes it easier for students to learn and provides fun and up-to-date things. Learning using science e-books based on local wisdom encourages students to learn actively and creatively because it is accompanied by exploratory tasks.